Age‐dependent changes in physical performance and body composition in community‐dwelling Japanese older adults. Issue 4 (8th June 2017) - Makizako, Hyuma; Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Lee, Sangyoon; Lee, Sung Chul; Harada, Kazuhiro; Hotta, Ryo; Nakakubo, Sho; Bae, Seongryu; Harada, Kenji; Yoshida, Daisuke; et al.
Abstract: Background: The aim of this study was to describe the age‐dependent changes in the parameters of physical performance and body composition in Japanese older adults who are independently dwelling in the community. We also examined whether the age‐dependent changes differ among physical performance and body composition parameters. Methods: Cross‐sectional data from 10 092 community‐dwelling older adults (mean age 73.6 years; 5296 women) were analyzed. The measures of physical performance included hand‐grip strength, the five‐times‐sit‐to‐stand test, and walking speed. Body composition parameters (body weight, fat mass, and appendicular skeletal muscle mass) were measured with a bioelectrical impedance analyser. Correlations between age and the physical performance and body composition parameters were tested. The T‐scores of physical performance and body composition measurements were calculated and presented according to 5‐year age groups to examine the differences in age‐dependent changes in physical performance and body composition parameters. Results: All physical performance measures significantly decreased with aging. The cumulative mean T‐scores according to age group showed different age‐dependent changes between body mass index (BMI) and appendicular skeletal muscle mass index (ASMI) (cumulative mean T‐score change of BMI and ASMI of −5.7 to −2.9 and −12.7 to −12.1, respectively). The slope declines in age‐associated changes were greater in grip strength ( β = −0.77, 95% confidence interval = −0.82 to −0.76) for men and in walking speed ( β = −0.95, 95% confidence interval = −0.99 to −0.90) for women. Conclusions: The patterns of age‐dependent decreases in physical performance measures differed among parameters and between sexes. There is a possibility of a difference in the age‐related slope patterns among parameters; decreases in grip strength in men and walking speed in women may be more prominent with advancing age. Furthermore, the decrease in ASMI with age is more striking than that of BMI.